University-Industry Interaction as an Element of the University’s «Third Mission» - E. V. Kudryashova; S. E. Sorokin; O. D. Bugaenko (Высшее образование в России)
In the context of the transformation of education, characterized by the rapid obsolescence of knowledge, the increasing role of technological and social innovations, the globalization of the economy and education, it is becoming increasingly important to ensure successful cooperation between universities and business. At the same time, the state gains an advantage due to the rapid transfer of new knowledge, research and innovation, enterprises and organizations increase opportunities for effective development.The aim of the study is to identify the most successful forms of interaction between educational organizations and enterprises, the mechanisms of influence of the University on the development of the region of its location, participation in socio-economic processes. The problem is considered through the prism of the concept of the “third mission” for universities, which involves active interaction of educational organizations with society, including employers. Besides, the authors use the provisions of the theory of stakeholders, which describes the parameters taking into account the interests of various actors in the process of University management.On the example of the Northern (Arctic) Federal University named after M.V. Lomonosov, the article analyzes the existing experience and successful practices of organizing such interaction, as well as the emerging problems. The information base of the study was a survey on the satisfaction of employers with the quality of University graduates’ training, conducted in SAFU in 2019.As findings, the article states the main systemic problems of interaction between universities and the sphere of production such as the lack of coordinated strategies for training in various specialties, discrepancies in understanding the sets of competencies and skills of graduates, the fragmented university-industry interaction in research and development areas, different motivations and values.The authors come to a conclusion that the University must undergo a path of transformation to ensure strategic interaction with business and industry, including the development of a common “entrepreneurial” culture in the team, as well as the expansion of interaction with public institutions and socio-economic actors in the framework of the “third mission”.